Returning Corrupt Assets Through International Cooperation: Joko Widodo's 10 Years in Power - Mansar, Adi; Dwilizadi, Vania Micha (DE LEGA LATA: JURNAL ILMU HUKUM, 2025)
The United Nations Convention Against Corruption (UNCAC) is a compact step by countries in the world to cooperate in the field of law and corruption, especially extradition and return of corruption proceeds that have been taken abroad. The follow-up to the birth of the convention for member countries is by ratifying it by making national regulations into Laws or Presidential Decrees. The Presidential Decree as the legal standing of corruption law politics, especially to obtain money as state income, is very useful, especially since the world is currently in a crisis. What is the state policy in returning corruption assets abroad? What form of legal efforts are effective and systematic in returning corruption proceeds? The research approach is taken comprehensively descriptively by using literature as a basis for research. The state policy since 2006 began with the ratification of existing regulations and the formation of regulations for the elimination of taxes to facilitate the return of funds to the country, forming a task force for the return of former BLBI assets to the formation of regulations for the confiscation of assets from corruption.